Aprendizaje por proyectos - Ubillus Salas, Paola Vanessa (2016)
The present article aims to show the importance of teaching by projects to materialize the objectives of the several pedagogical proposals, since the demands of today's world require developing research skills to be able to investigate, organize and summarize a lot of information that is finally relevant or significant for the student and can apply it in the solution of an aspect in reality. This opportunity gives us the learning projects and for them, teachers must be not only  methodologically prepared but also know how synergies work in the classroom.